Study on the vulnerability and resilience of Caribbean Small Island Developing States (SIDS) - NU. CEPAL. Sede Subregional para el Caribe (ECLAC, Subregional Headquarters for the Caribbean, 2015)
Caribbean Small Island Developing States are considered to be particularly vulnerable to external shocks that stem from changes in climate and the increase in frequency and magnitude of natural disasters. Quantification of the extent of vulnerability of these islands may be measured by the use of several indices including the Economic Vulnerability Index (EcVI), the Disaster Deficit Index (DDI), the Environmental Vulnerability Index (EVI) and the Social Vulnerability Index (SVI). The capacity to build resilience may be measured by the Economic Resilience Index (ERI). Of importance in the measurement of vulnerability and resilience is the impact on women and children. In order to reduce vulnerability and promote resilience, Caribbean SIDS are urged to develop adaptation strategies. Such strategies include the conduct of indepth studies on natural environmental impacts specifically in terms of biophysical and socio economic impacts. It is also necessary to review best practices in terms of preparedness, resilience building and climate change adaptation in other countries such as Cuba. Addressing vulnerability and building resilience requires appropriate information and data and priority should be given to addressing data gaps. It would also be expedient to classify vulnerability and resilience as regional public goods wherein one country’s benefit does not compromise another country’s ability to benefit. Finally, it is important to acknowledge that vulnerability is, in part, is a function of gender so that indicators need to be disaggregated to reflect the country-specific gendered socioeconomic situation.